PHYTOCHEMICAL STUDY OF THE LEAVES OF Jacaranda caroba (Vell.) DC. - Collantes Díaz, Ingrit Elida (2016)
Jacaranda caroba is a tree native to Brazil, commonly used in Brazilian traditional medicine. Phytochemical study made with the chloroform residue obtained from 70% ethanol extract of the leaves led to the isolation and identification of pentacyclic triterpenes 3-epi-corosolic acid (1), 2α,3α,19α-trihydroxyurs-12-en-28-oic acid (2), 2α-hydroxyursolic acid (3), maslinic acid (4), 2α,3α,23-trihydroxyurs-12-en-28-oic acid (5), 2α,3α,23-trihydroxyolean-12-en-28- oic acid (6), 2α,3β,23-trihydroxyolean-12-en-28-oic acid (7), 2α,3α,24-trihydroxyurs-12-en- 28-oic acid (8) and 2α,3α,24-trihydroxyolean-12-en-28-oic acid (9), identified by literature comparison of their 1H-NMR and 13C-NMR.